Temporal muscle flap in reconstruction of maxillo-facial tissues - Krzymański, Grzegorz; Dąbrowski, Jarosław; Przybysz, Jan; Domański, Wojciech; Biernacka, Barbara; Piętka, Tomasz (Contemporary Oncology/Współczesna Onkologia, 2012)
Aim of the study: Presents our experience in reconstruction of postsurgical defects with use of temporal muscle flap. Material and methods: In the years 1996–2010 we treated 10 patients with malignant neoplasms of maxillo-facial region. Following tumor removal the fascia-muscle flaps of temporal muscle were used for reconstruction. Temporal muscle flaps were applied in 5 cases for reconstructing the defect of eye socket tissue after extensive resections and in the other 5 patients was used for reconstructing the defect of palate following maxillary resections. Results : All the flaps of temporal muscle that were used for reconstructing eye sockets incorporated with no local reaction. In one case of flap applied into the oral cavity for tightly separate from nasal, partial necrosis of flap’s edge and oro-nasal fistula occurred. Conclusions : Fascia-muscular flap of temporal muscle is a simple, easy and effective method of tissue reconstruction in maxillo-facial region following extensive oncologic procedures.